FUNERAL ARCHITECTURE OF ARCHEOLOGICAL MONUMENTS OF «KULAZHORGA» TYPE - Abzalbekov, M.; Zhumatayev, R. (Journal of history, 2018)
The burial rite is one of the key elements of the culture of any ethnos. In recent decades, the grave facilities of nomadic peoples and stone ritual-cult objects have become the subject of close study in this context. From a rather little-known and exotic subject of study, they have turned into objects of interest of a wide range of researchers, they are paid close attention to specialists in the field of architecture. Archaeological monuments of the “Kulazhorga” type in the first were singled out by S.Chernikov as a special stage of the Early Iron Age of East Kazakhstan. To date, a huge amount of material has been accumulated on these monuments. But the architectural features have not been fully explored. Therefore, the purpose of this paper is to determine the structure of the location and funeral rites of kurgans of the Kulazhorga type. The task of the study is to determine the specifics of the manifestation of the burial rite, as well as the dynamics of the development of structural features of land and intramobile structures.